BOND STRENGTH OF SELF-ETCH ADHESIVES WITH PRIMARY AND PERMANENT TEETH DENTIN - IN VITRO STUDY. - Natalia Gateva; Valentin Dikov (Peytchinski Publishing, 2012)
Objective: The aim of this study was to compare dentin bond strength of primary and permanent teeth with self-etching adhesive systems. Methods: On 40 intact specimens of primary and permanent teeth was created flat dentin surfaces. The patterns were divided in 4 groups. Two different self-etching adhesive systems were used - one two steps (AdheSE, VivaDent) and one one step (AdheSE One, VivaDent). Resin composite build-ups were constructed by means of convetional copper ring after applying the adhesive. The specimens were stored in water for 72 h at room temperature. After that specimens were tested for macrotensile bond strength. Debonded surfaces were analyzed by SEM.Conclusions: The measured values of dentin bond strength after applying self-etching adhesives are statistically significant in group of permanent teeth in comparison with group of primary teeth, and for both adhesive generations. Two steps self-etching adhesive provide significant stronger dentin bond strength with both dentitions in comparison with one step self-etching adhesive.